Hesitação vacinal infantil e fatores associados: estudo em Região Metropolitana do nordeste brasileiro no contexto pandêmico - LIMA, Joseanna Gomes (2022)
Vaccination hesitancy is not a current phenomenon. The immunization itself was started simultaneously. However, over time, it has evolved according to changes in the social contexts of which it is a part. It is defined as the delay in accepting or refusing vaccines, even if they are available in vaccination services. The objective of this research is to evaluate the prevalence of childhood vaccination hesitancy and its associated factors in a municipality in the Metropolitan Region of Maranhão during the COVID-19 pandemic. This is a descriptive study with a cross-sectional design and a quantitative approach. The research was carried out in Paço do Lumiar, a municipality belonging to the Metropolitan Region of Greater São Luís - MA. The investigated sample consisted of 246 family members or caregivers of children under 5 years of age. Data collection was carried out in the coverage areas of the seventeen Basic Health Units belonging to Primary Health Care in the municipality. A structured questionnaire was used to characterize the socioeconomic and demographic profile, biosafety aspects and health conditions against COVID-19 of 246 participants. The “Instrument to study childhood vaccine hesitancy applied to parents or caregivers, developed by the Strategic Advisory Group of Experts Working Group on Vaccine Hesitancy” was also applied. A quarter of family members (25.2%) hesitated to vaccinate their children (score ≤39 points) and 74.8% did not hesitate (score ≥ 40 points). The single marital status variable was a factor associated with risk (OR =2.03 p = 0.039) and updated COVID-19 vaccination had a lower prevalence association (OR = 0.10 p < 0,001) with hesitation to vaccinate childish. Considerable immunization hesitant behavior was identified among parents or caregivers. The development of strategies and actions with the dissemination of scientific information for greater adherence to vaccination and reduction of morbidity and mortality in the child population should be considered.